Electrode sheet for lithium-ion secondary batteries

JP7645372B2Active Publication Date: 2025-03-13TEIJIN LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023525823
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-31
Filing Date
2022-05-30
Publication Date
2025-03-13
Estimated Expiration
2042-05-30

AI Technical Summary

Benefits of technology

【0019】 本発明のリチウムイオン二次電池用電極シートは、その製造工程において、成膜するための溶媒を使用しないため、製造が簡便である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645372000002
    Figure 0007645372000002
  • Figure 0007645372000003
    Figure 0007645372000003
  • Figure 0007645372000004
    Figure 0007645372000004
Patent Text Reader

Abstract

The present invention provides an electrode sheet for a lithium ion secondary battery containing at least a lithium ion battery active material, fibrous carbon, and a fluorine-based polymer. This electrode sheet for a lithium ion secondary battery is characterized by having the film thickness of 50-2000 (μm), the tensile breaking strength of at least 0.2 (N / mm2), the average fiber diameter of the fibrous carbon of 100-900 (nm), and the fibrous carbon content of 0.1-10 (mass%) in the electrode sheet.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode sheet for lithium ion secondary batteries that contains at least an active material for lithium ion batteries, fibrous carbon, and a fluorine-based polymer. [Background technology]

[0002] Lithium-ion secondary batteries are secondary batteries in which lithium ions in an electrolyte are responsible for electrical conduction, and the mainstream batteries use lithium metal oxide as the electrode active material for the positive electrode and carbon materials such as graphite as the electrode active material for the negative electrode. Lithium-ion secondary batteries have the characteristic of having a high energy density among secondary batteries, and so their range of applications is expanding from small devices such as mobile phones to large devices such as electric vehicles.

[0003] The electrode sheet for lithium ion secondary batteries is generally produced by preparing a slurry containing an active material for lithium ion batteries, a conductive assistant, a binder, and a solvent, applying the slurry as a thin film, and then removing the solvent. Therefore, a slurry preparation process for uniformly dispersing the active material for lithium ion batteries, a conductive assistant, a binder, and a solvent, and a drying process for removing the solvent are required, which makes the manufacturing process complicated. In addition, cracks are likely to occur in the electrode sheet during the drying process for removing the solvent, making it difficult to increase the thickness of the electrode sheet. Furthermore, fibrous carbon is sometimes used as a conductive assistant for the purpose of improving conductivity, but fibrous carbon with a large aspect ratio is likely to be oriented in the coating direction during the process of applying a thin film of the slurry. As a result, anisotropy is likely to occur in the mechanical strength of the electrode sheet.

[0004] Patent Document 1 describes that a slurry is prepared using lithium cobalt oxide as a positive electrode active material, polyvinylidene fluoride as a binder, acetylene black as a conductive material, and N-methylpyrrolidone as a solvent, and that the slurry is then applied, dried, and roll-pressed to prepare a positive electrode. Patent Documents 2 and 3 disclose a dry film produced by fibrillating polytetrafluoroethylene using a rolling device, but there is no description of the use of fibrous carbon. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2014 / 115852 [Patent Document 2] Special Publication No. 2020-522090 [Patent Document 3] Special Publication No. 2021-504877 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an electrode sheet for a lithium ion secondary battery that can be produced without using a solvent, and a method for producing the same. [Means for solving the problem]

[0007] As a result of extensive research in light of the above-mentioned conventional technology, the inventors have found that the above-mentioned problems can be solved by using a specific type of fibrous carbon in an electrode sheet and a fluorine-based polymer as a binder, and have thus completed the present invention. That is, the electrode sheet of the present invention is an electrode sheet supported by a fluoropolymer, and is characterized in that no solvent is used for film formation in the production process.

[0008] The present invention, which solves the above problems, is as described below.

[0009] [1] An electrode sheet for a lithium ion secondary battery, comprising at least an active material for a lithium ion battery, fibrous carbon, and a fluorine-based polymer, The thickness of the electrode sheet for lithium ion secondary batteries is 50 to 2000 (μm), and the tensile breaking strength is 0.20 (N / mm 2 ) or more, The average fiber diameter of the fibrous carbon is 100 to 900 (nm), The electrode sheet for a lithium ion secondary battery, wherein the content of the fibrous carbon in the electrode sheet for a lithium ion secondary battery is 0.1 to 10 (mass %).

[0010] The invention described in [1] above is an electrode sheet for lithium ion secondary batteries in which the sheet form is maintained by a fluoropolymer. This electrode sheet is an electrode sheet called a dry film, which is manufactured without going through a slurry.

[0011] [2] The electrode sheet for a lithium ion secondary battery according to [1], further comprising a carbon-based conductive assistant other than the fibrous carbon.

[0012] The invention described in [2] above further includes a carbon-based conductive additive other than fibrous carbon. The carbon-based conductive additive here does not mean fibrous carbon that differs only in the average fiber diameter defined in [1].

[0013] [3] The electrode sheet for a lithium ion secondary battery according to [1], wherein the average fiber length of the fibrous carbon is 10 to 50 (μm).

[0014] [4] The packing density of the fibrous carbon is 0.8 (g / cm 3 ) powder volume resistivity is 4.00×10 -2 (Ω·cm) or less.

[0015] [5] The electrode sheet for a lithium ion secondary battery according to [1], wherein the fluorine-based polymer is polytetrafluoroethylene.

[0016] [6] The electrode sheet for lithium ion secondary batteries according to [1], wherein the electrode sheet for lithium ion secondary batteries has a porosity of 5 to 60 (volume %).

[0017] [7] The tensile breaking strength (N / mm 2 The electrode sheet for lithium ion secondary batteries according to [1], wherein the product of the thickness (mm) and the thickness (mm) is 0.04 (N / mm) or more.

[0018] [8] The electrical conductivity of the electrode sheet for lithium ion secondary batteries in the thickness direction is 8.0 × 10 -4 (S / cm) or more. Effect of the Invention

[0019] The electrode sheet for lithium ion secondary batteries of the present invention can be easily produced since no solvent is used for film formation in the production process. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is an SEM photograph (5000x magnification) showing the surface of the electrode sheet obtained in Example 1. [Diagram 2] FIG. 2 is an SEM photograph (5000x) showing a cross section of the electrode sheet obtained in Example 1. [Diagram 3] FIG. 3 is an SEM photograph (5000x magnification) showing the surface of the electrode sheet obtained in Example 2. [Figure 4] FIG. 4 is an SEM photograph (5000x) showing a cross section of the electrode sheet obtained in Example 2. [Diagram 5] FIG. 5 is an SEM photograph (5000x) showing the surface of the electrode sheet obtained in Comparative Example 1. [Figure 6] FIG. 6 is an SEM photograph (5000x) showing a cross section of the electrode sheet obtained in Comparative Example 1. [Figure 7]FIG. 7 is an SEM photograph (5000x) showing the surface of the electrode sheet obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] (1) Electrode sheet for lithium-ion secondary batteries The electrode sheet for lithium ion secondary batteries (hereinafter sometimes abbreviated as "electrode sheet") of the present invention contains at least an active material for lithium ion batteries, fibrous carbon, and a fluoropolymer. In the electrode sheet of the present invention, it is preferable that the fluoropolymer is dispersed in the electrode sheet, including a fibrous form. Specifically, it is preferable that the fluoropolymer is partially or entirely fibrillated, and the fibrillated fluoropolymer is dispersed so as to cooperate with the fibrous carbon to maintain the shape of the electrode sheet. In particular, it is more preferable that the electrode sheet is configured so that the fibrillated fluoropolymer and the fibrous carbon are entangled to support the fibrous carbon and form voids by the fibrous carbon. By configuring the electrode sheet in this way, it is possible to obtain a configuration that allows the volume fluctuation of the active material in the electrode sheet to be tolerated while maintaining the shape stability of the electrode sheet as a whole by the fibrous carbon having a predetermined fiber length.

[0022] The thickness of the electrode sheet is 50 to 2000 μm. The thickness of the electrode sheet is preferably 80 μm or more, and more preferably 100 μm or more, 120 μm or more, 150 μm or more, 180 μm or more, 200 μm or more, 250 μm or more, and 300 μm or more in this order. If the thickness is less than 50 μm, it becomes difficult to maintain the sheet shape. In addition, when manufacturing a high-capacity cell, a large amount of separator and current collector are used, and as a result, the volume occupancy rate of the electrode sheet in the cell decreases. This is not preferable from the viewpoint of energy density, and the application is significantly limited. In particular, it becomes difficult to apply it to power source applications that require high energy density. From the viewpoint of stable production of the electrode sheet, the thickness of the electrode sheet is 2000 μm or less. The thickness of the electrode sheet is preferably 1500 μm or less, more preferably 1200 μm or less, 1000 μm or less, 800 μm or less, 600 μm or less, 500 μm or less, and 400 μm or less in this order.

[0023] The tensile breaking strength of the electrode sheet is 0.20N / mm 2 The tensile strength is preferably 0.25 N / mm 2 More preferably, it is 0.30 N / mm 2 More than 0.40N / mm 2 More than 0.50N / mm 2 More than 0.60N / mm 2 More than 0.65N / mm 2 The preferred order is 0.20N / mm or more. 2 If the capacity is less than 100%, the handling of the battery is likely to be deteriorated, and the battery performance is likely to be deteriorated due to the volume change of the active material accompanying the charging and discharging of the lithium ion secondary battery. The upper limit of the tensile breaking strength of the electrode sheet is not particularly limited, but is generally 10.0 N / mm 2 The tensile strength is 5.0N / mm 2 It is preferable that the resistance is less than 3.0N / mm 2 Below, 2.0N / mm 2 Below, 1.5N / mm 2 Below, 1.0N / mm 2 The following are preferred in this order:

[0024] Tensile breaking strength of electrode sheet (N / mm 2 The product of the thickness (mm) and the film thickness is preferably 0.04 (N / mm) or more, more preferably 0.05 (N / mm) or more, 0.06 (N / mm) or more, 0.08 (N / mm) or more, 0.1 (N / mm) or more, 0.15 (N / mm) or more, and 0.2 (N / mm) or more in this order. If it is less than 0.04 (N / mm), it is difficult to maintain the sheet shape. Tensile breaking strength of electrode sheet (N / mm 2The upper limit of the product of the thickness (mm) and the thickness is not particularly limited, but is generally 5.0 (N / mm) or less, and is preferably 3.0 (N / mm) or less, 2.0 (N / mm) or less, 1.5 (N / mm) or less, 1.0 (N / mm) or less, 0.8 (N / mm) or less, 0.6 (N / mm) or less, 0.5 (N / mm) or less, and 0.4 (N / mm) or less, in that order. If it exceeds 5.0 (N / mm), the blending ratio of the fluorine-based polymer used as the binder increases, and the blending ratio of the active material decreases relatively, which tends to deteriorate the battery performance.

[0025] The electrical conductivity of the electrode sheet in the thickness direction is 8.0×10 -4 The electrical conductivity is preferably 1.0×10 S / cm or more. -3 S / cm or more is preferable, and 1.5×10 -3 S / cm or more, 3.0×10 -3 S / cm or more, 5.0×10 -3 S / cm or more, 7.0×10 -3 S / cm or more, 9.0×10 -3 S / cm or more, 1.0×10 -2 It is preferable that the electrical conductivity is 1.0 S / cm or more, in this order. Such an electrical conductivity can be achieved by including a specific fibrous carbon as a conductive assistant.

[0026] The electrical conductivity σ (S / cm) in the thickness direction of the electrode sheet divided by the content Xc (mass%) of the carbon-based conductive additive is 1.0×10 -4 More preferably, it is equal to or greater than this. σ / Xc is 1.5×10 -4 More preferably, it is 2.0×10 or more. -4 That's it, 3.0 x 10 -4 That's it, 4.0 x 10 -4 That's it, 5.0 x 10 -4 More preferably, σ / Xc is 1.0×10 or more. -4 If the content of the carbon-based conductive additive is less than 1.0×10, the content of the carbon-based conductive additive must be excessive, which is not preferable from the viewpoint of improving the energy density. -2 The following is the result.

[0027] The apparent density of the electrode sheet is 1.0 to 3.0 g / cm 3 The apparent density is preferably 1.2 g / cm 3 More preferably, it is 1.5 g / cm or more. 3 More than 1.8g / cm 3 More than 2.0g / cm 3 More preferably, the apparent density of the electrode sheet is 2.8 g / cm or more. 3 More preferably, it is 2.5 g / cm or less. 3 Below, 2.2g / cm 3 More preferably, the apparent density of the electrode sheet is in this range, in that order. By setting the apparent density of the electrode sheet in this range, the occurrence of cracks in the electrode sheet is particularly suppressed even when charge / discharge cycles accompanied by volume changes of the active material are repeated. In addition, the true density of the electrode sheet is 2.0 to 4.0 g / cm 3 and preferably 3.0 to 3.7 g / cm 3 It is more preferable that the apparent density of the electrode sheet is the density calculated by the formula (2) described below.

[0028] The electrode sheet has voids. The porosity is preferably 5.0% by volume or more and 60% by volume or less. When the porosity is in this range, even if charge / discharge cycles accompanied by volume changes of the active material are repeated, the occurrence of cracks in the electrode sheet is particularly suppressed. By using an electrode sheet having such voids, a lithium ion secondary battery with particularly high electronic conductivity and ionic conductivity and high output can be constructed. The porosity is preferably 10% by volume or more, and particularly preferably 15% by volume or more, 20% by volume or more, 25% by volume or more, 30% by volume or more, and 35% by volume or more in this order. The upper limit of the porosity is preferably 55% by volume or less, more preferably 50% by volume or less, and particularly preferably 45% by volume or less.

[0029] The porosity of the electrode sheet can be adjusted by controlling the materials, sizes and contents of the fibrous carbon, fluoropolymer and active material, as well as the molding conditions when producing the electrode sheet.

[0030] The method for calculating the porosity is not particularly limited, but examples include a method of calculating the porosity based on the apparent density and true density of the electrode sheet based on the following formula (1), and a method of calculating the porosity from a three-dimensional image obtained by tomography such as X-ray CT. Porosity (volume%) = (true density - apparent density) / true density × 100 Formula (1)

[0031] When calculating based on formula (1), the true density and apparent density are measured. The true density can be measured, for example, based on the true density and mass ratio of each material constituting the electrode sheet, or by measuring the electrode sheet after crushing it using a gas phase displacement method (pycnometer method) or a liquid phase method (Archimedes method). The apparent density of the electrode sheet can be calculated, for example, from the mass and volume of the electrode sheet using the following formula (2). Apparent density of electrode sheet = Mass of electrode sheet / (Thickness of electrode sheet × Area) Equation (2)

[0032] (1-2) Active material The electrode sheet of the present invention contains at least a positive electrode active material or a negative electrode active material.

[0033] <Cathode active material> The positive electrode active material contained in the electrode sheet of the present invention can be one or more selected from lithium-containing metal oxides capable of absorbing and releasing lithium ions in a lithium ion secondary battery. Examples of the lithium-containing metal oxide include composite oxides containing lithium and at least one element selected from the group consisting of Co, Mg, Mn, Ni, Fe, Al, Mo, V, W, Ti, etc.

[0034] Specifically, Li x CoO2, Lix NiO2, Li x MnO2, Li x Co a Ni 1-a O2, Li x Co b V 1-b O z , Li x Co b Fe 1-b O2, Li x Mn2O4, Li x Mn c Co 2-c O4, Li x Mn c Ni 2-c O4, Li x Mn c V 2-c O4, Li x Mn c Fe 2-c The lithium-containing metal oxide may be at least one selected from the group consisting of LiFePO4 (wherein x=0.02 to 1.2, a=0.1 to 0.9, b=0.8 to 0.98, c=1.2 to 1.96, and z=2.01 to 2.3), LiFePO4, and the like. x CoO2, Li x NiO2, Li x MnO2, Li x Co a Ni 1-a O2, Li x Mn2O4, Li x Co b V 1-b O z (wherein x, a, b, and z are the same as above), and LiFePO4. The value of x is the value before the start of charging and discharging, and increases or decreases due to charging and discharging.

[0035] The positive electrode active material may be used alone or in combination of two or more. The average particle size of the positive electrode active material is preferably 10 μm or less, more preferably 0.05 to 7 μm, and even more preferably 1 to 7 μm. If the average particle size exceeds 10 μm, the efficiency of the charge / discharge reaction under a large current may decrease.

[0036] The content of the positive electrode active material in the electrode mixture layer of the present invention is preferably 60% by mass or more, more preferably 70 to 98.5% by mass, and even more preferably 75 to 98.5% by mass. If it is less than 60% by mass, it may be difficult to apply it to power sources that require high energy density. If it exceeds 98.5% by mass, the amount of fluorine-based polymer is too small, so that cracks may occur in the electrode mixture layer or the electrode mixture layer may peel off from the current collector. Furthermore, the amount of fibrous carbon or carbon-based conductive assistant may be too small, so that the conductivity of the electrode mixture layer may be insufficient.

[0037] <Negative electrode active material> The negative electrode active material contained in the electrode sheet of the present invention can be one or more of any of the conventionally known materials known as negative electrode active materials in lithium ion secondary batteries. For example, as a material capable of absorbing and releasing lithium ions, a carbon material, any of Si and Sn, or an alloy or oxide containing at least one of them can be used. Among these, carbon materials are preferred from the viewpoint of cost and the like. Examples of the carbon material include natural graphite, artificial graphite produced by heat treatment of petroleum-based or coal-based coke, hard carbon obtained by carbonizing resin, and mesophase pitch-based carbon materials.

[0038] When natural graphite or artificial graphite is used, it is preferable that the interplanar spacing d(002) of the (002) plane of the graphite structure by powder X-ray diffraction is in the range of 0.335 to 0.337 nm from the viewpoint of increasing the battery capacity. Natural graphite refers to a graphitic material that occurs naturally as an ore. Depending on its appearance and properties, natural graphite is divided into two types: scaly graphite with a high degree of crystallinity and earthy graphite with a low degree of crystallinity. Scaly graphite is further divided into flake graphite with a leaf-like appearance and scaly graphite with a lump-like appearance. There are no particular limitations on the place of origin, properties, or type of natural graphite that becomes the graphitic material. In addition, natural graphite or particles produced from natural graphite as a raw material may be heat-treated before use.

[0039] Artificial graphite refers to graphite and graphitic materials that are close to perfect crystals of graphite, which are widely made by artificial methods. A typical example is graphite obtained by using tar and coke obtained from the residues of coal dry distillation and crude oil distillation as raw materials, and going through a baking process at about 500 to 1000 °C and a graphitization process at 2000 °C or higher. Kish graphite, which is obtained by reprecipitating carbon from molten iron, is also a type of artificial graphite.

[0040] The use of an alloy containing at least one of Si and Sn in addition to a carbon material as the negative electrode active material is effective in that the electric capacity can be reduced compared to the case where Si and Sn are used alone or the case where the oxides of each are used. Among these, Si-based alloys are preferable. Examples of Si-based alloys include alloys of at least one element selected from the group consisting of B, Mg, Ca, Ti, Fe, Co, Mo, Cr, V, W, Ni, Mn, Zn, and Cu, and Si. Specifically, at least one element selected from the group consisting of SiB4, SiB6, Mg2Si, Ni2Si, TiSi2, MoSi2, CoSi2, NiSi2, CaSi2, CrSi2, Cu5Si, FeSi2, MnSi2, VSi2, WSi2, and ZnSi2 can be mentioned.

[0041] In the electrode sheet of the present invention, the above-mentioned materials may be used alone or in combination as the negative electrode active material. The average particle size of the negative electrode active material is 10 μm or less. If the average particle size exceeds 10 μm, the efficiency of the charge / discharge reaction under a large current is reduced. The average particle size is preferably 0.1 to 10 μm, and more preferably 1 to 7 μm.

[0042] The content of the negative electrode active material in the electrode sheet is not particularly limited, but is preferably 30 to 99 mass%, more preferably 40 to 99 mass%, and even more preferably 50 to 95 mass%. If it is less than 30 mass%, it may be difficult to apply the electrode sheet to power sources that require high energy density.

[0043] (1-3) Fibrous carbon The fibrous carbon used in the present invention is preferably a carbon fiber, and more preferably a pitch-based carbon fiber made from pitch as a starting material, in that it has excellent electrical conductivity.

[0044] The average fiber diameter of the fibrous carbon is 100 to 900 nm. The lower limit of the average fiber diameter is preferably 200 nm or more, more preferably more than 200 nm, more preferably 220 nm or more, and even more preferably 250 nm or more. The upper limit of the average fiber diameter is preferably 700 nm or less, more preferably 600 nm or less, more preferably 500 nm or less, more preferably 400 nm or less, and more preferably 350 nm or less. If it is less than 100 nm, the fibers are easily broken and do not function as a conductive material. In addition, fibrous carbon with an average fiber diameter of less than 100 nm has a large specific surface area and covers the surface of the active material in the electrode sheet. As a result, the contact points of the active material are reduced, which leads to the inhibition of the formation of an ion conduction path. Fibrous carbon with an average fiber diameter of more than 900 nm is likely to cause gaps between the fibers in the electrode sheet, which may make it difficult to increase the electrode sheet density.

[0045] The fiber diameter distribution of the fibrous carbon exhibiting an average fiber diameter of 100 to 900 nm may have one peak or two or more peaks at 100 to 900 nm, but usually preferably has one peak.

[0046] The aspect ratio of the fibrous carbon (average fiber length / average fiber diameter) is 30 or more, preferably 35 or more, and preferably 40 or more. If the aspect ratio is less than 30, when the electrode sheet is manufactured, the formation of a conductive path by the fibrous carbon in the electrode sheet is likely to be insufficient, and the resistance value in the thickness direction of the electrode sheet may not be sufficiently reduced. In addition, the mechanical strength of the electrode sheet is likely to be insufficient. The upper limit of the aspect ratio is not particularly limited, but is preferably 1000 or less, more preferably 500 or less, and even more preferably 300 or less. If the aspect ratio is too large, the fibrous carbon may be entangled with each other and may not be sufficiently dispersed in the electrode sheet, and the formation of a conductive path may be insufficient.

[0047] The average fiber length of the carbon fiber used in the present invention is preferably 10 μm or more, more preferably 11 μm or more, even more preferably 12 μm or more, even more preferably 13 μm or more, and particularly preferably 15 μm or more. The average fiber length is preferably 100 μm or less, more preferably 80 μm or less, and particularly preferably 50 μm or less. By having fibrous carbon with such an average fiber length present in the electrode sheet, voids are formed around the fibrous carbon, allowing the volume fluctuation of the active material, and the conductive path can be maintained by following both the increase and decrease in the volume of the active material, and further, the electrode sheet becomes tough, so that the decrease in strength and the decrease in apparent density can be suppressed. When an electrode sheet is manufactured using carbon fibers with an average fiber length of less than 10 μm, the formation of the conductive path in the electrode sheet is likely to be insufficient, and the resistance value in the thickness direction of the electrode sheet may not be sufficiently reduced. When an electrode sheet is produced using fibrous carbon with an average fiber length exceeding 100 μm, the fibrous carbon tends to be oriented in the in-plane direction in the electrode sheet, which may make it difficult to form a conductive path in the thickness direction.

[0048] The fibrous carbon used in the present invention preferably has a structure that is substantially free of branches. Here, substantially free of branches means that the degree of branching is 0.01 pieces / μm or less. The fibrous carbon in the present invention preferably has a degree of branching of 0. Here, branching refers to a granular portion in which the fibrous carbon is bonded to other fibrous carbon at a location other than the terminal portion, and refers to the main axis of the fibrous carbon being branched in the middle, and the main axis of the fibrous carbon having a branched sub-axis. As a branched fibrous carbon, for example, vapor-phase grown (vapor-phase method) carbon fiber (for example, VGCF (registered trademark) manufactured by Showa Denko KK) produced by a vapor phase method in which a hydrocarbon such as benzene is vaporized in a high-temperature atmosphere in the presence of a metal such as iron as a catalyst is known. Fibrous carbon having a linear structure that is substantially free of branching has good dispersibility compared to fibrous carbon having branches, and is easy to form a long-distance conductive path. In addition, the linear structure includes a case in which the fibrous carbon has a completely linear structure, a case in which one end or both ends are slightly bent, and a case in which the parts other than both ends are slightly bent.

[0049] Here, the degree of branching of the fibrous carbon used in the present invention means a value measured from a photograph taken at a magnification of 5,000 times by a field emission scanning electron microscope.

[0050] In addition, this fibrous carbon may have a fibrous form as a whole, and includes, for example, carbon having an aspect ratio less than the preferred range above that is in contact or bonded together to form an integrated fibrous shape (for example, carbon globules strung together like beads, or at least one or more extremely short fibers connected by fusion or the like).

[0051] The fibrous carbon used in the present invention has high electrical conductivity even when the packing density is low. The fibrous carbon having high electrical conductivity even when the packing density is low can impart electrical conductivity at a lower addition concentration.

[0052] Specifically, the packing density is 0.8 g / cm 3 The powder volume resistivity when filled is 4.00×10 -2It is preferable that the resistance is Ω·cm or less, and 3.00×10 -2 It is more preferable that the resistivity is 4.00×10 Ω·cm or less. -2 If the electrical conductivity exceeds Ω·cm, the amount of fibrous carbon required to improve the electrical conductivity will increase, which is not desirable. There is no particular lower limit, but the lower limit is generally about 0.0001 Ω·cm.

[0053] The fibrous carbon used in the present invention has a distance (d002) between adjacent graphite sheets measured by wide-angle X-ray measurement of preferably 0.3400 nm or more, more preferably more than 0.3400 nm, even more preferably 0.3410 nm or more, and even more preferably 0.3420 nm or more. In addition, d002 is preferably 0.3450 nm or less, and more preferably 0.3445 nm or less. When d002 is 0.3400 nm or more, the fibrous carbon is less likely to become brittle. Therefore, during processing such as crushing, the fibers are less likely to break, and the fiber length is maintained. As a result, it becomes easier to form a conductive path over a long distance. In addition, the conductive path is easily maintained by following the volume change of the active material accompanying the charge and discharge of the lithium ion secondary battery.

[0054] The fibrous carbon used in the present invention preferably has a crystallite size (Lc002) of 50 nm or less, more preferably 40 nm or less, 30 nm or less, and 25 nm or less, in that order, as measured by wide-angle X-ray measurement. The larger the crystallite size (Lc002), the higher the crystallinity and the better the electrical conductivity. However, when the crystallite size (Lc002) is large, the fibrous carbon is less likely to become brittle. Therefore, the fibers are less likely to break during processing such as crushing, and the fiber length is maintained. As a result, it is easy to form a long-distance conductive path. In addition, the conductive path is easily maintained by following the volume change of the active material accompanying the charge and discharge of the all-solid-state lithium secondary battery. There is no particular limit to the lower limit of the crystallite size (Lc002), but it is preferably 1 nm or more. In the present invention, the crystallite size (Lc002) refers to a value measured according to Japanese Industrial Standard JIS R 7651 (2007 edition) "Method of measuring lattice constant and crystallite size of carbon materials."

[0055] The specific surface area of ​​the fibrous carbon used in the present invention is 1 m 2 / g or more 50m 2 / g or less. 2 If it is less than 1 / g, it is difficult to ensure contact between the active material and the fibrous carbon serving as the conductive additive, and an electron conductive path may not be sufficiently formed. On the other hand, if the specific surface area is too large, it may obstruct the ion conduction path. 2 If the specific surface area exceeds 2 m / g, the fibrous carbon covers the surface of the active material, reducing the number of contact points between the active material and the solid electrolyte responsible for ion conduction, which may inhibit ion conduction. 2 / g or more, and 2 / g or more is more preferable, and 5m 2 / g or more is more preferable, 2 / g or more. The upper limit of the specific surface area is 40 m 2 / g or less, and 2 / g or less is more preferable, and 25m 2 / g or less is more preferable, 2 It is particularly preferable that the molecular weight is not more than 1 / g.

[0056] The fibrous carbon used in the present invention preferably does not substantially contain metal elements. Specifically, the total content of metal elements is preferably 50 ppm or less, more preferably 30 ppm or less, and even more preferably 20 ppm or less. When the content of metal elements exceeds 50 ppm, the catalytic action of the metal easily deteriorates the battery. In the present invention, the content of metal elements means the total content of Li, Na, Ti, Mn, Fe, Ni, and Co. In particular, the content of Fe is preferably 5 ppm or less, more preferably 3 ppm or less, and even more preferably 1 ppm or less. When the content of Fe exceeds 5 ppm, it is not preferable because the battery is easily deteriorated.

[0057] The fibrous carbon used in the present invention preferably has hydrogen, nitrogen and ash content of 0.5% by mass or less, more preferably 0.3% by mass or less, in the fibers. When the hydrogen, nitrogen and ash content of the fibrous carbon are each 0.5% by mass or less, structural defects in the graphite layer are further suppressed, and side reactions in the battery can be suppressed, which is preferable.

[0058] The fibrous carbon used in the present invention has particularly excellent dispersibility in the electrode sheet. The reason for this is not clear, but it is thought that it has the above-mentioned structure, uses artificial graphite, non-graphitizable carbon, and graphitizable carbon produced by heat treating natural graphite, petroleum-based and coal-based coke, as raw materials, and uses resin composite fibers in the manufacturing process. Since it has excellent dispersibility in the electrode sheet, it is possible to form a long-distance conductive path, and it is thought that a small content of the carbon fiber provides excellent battery performance.

[0059] The fibrous carbon used in the present invention may have a porous or hollow structure, but in the manufacturing process of the fibrous carbon, it is preferable to go through a resin composite fiber obtained by melt blend spinning. Therefore, it is preferable that the fibrous carbon of the present invention is substantially solid, has a basically smooth surface, and has a linear structure without branches as described above.

[0060] The surface of the carbon fiber used in the present invention may be modified chemically or physically. The modifying substance and the type of modification are not particularly limited, and a suitable one may be selected according to the purpose of the modification.

[0061] The modification of the carbon fiber will be described below. By modifying the surface of the fibrous carbon with a thermoplastic resin, it is possible to impart adhesiveness to the fibrous carbon. The modification method is not particularly limited, but examples thereof include a method of attaching and / or adhering a particulate thermoplastic resin to the surface of the fibrous carbon; a method of bonding the fibrous carbon and the thermoplastic resin so that the fibrous carbon penetrates the particulate thermoplastic resin; and a method of covering a part of the surface of the fibrous carbon with a thermoplastic resin. In particular, it is preferable to attach at least a part of the thermoplastic resin in a particulate form. Here, particulate means a particle having an aspect ratio of 5 or less, preferably 2 or less, more preferably 1.5 or less. Specific modification methods include a method of spray-drying the fibrous carbon dispersed in a solution of a thermoplastic resin, a method of mixing the fibrous carbon with a monomer solution to polymerize the monomer, and a method of precipitating the thermoplastic resin in a solvent in which the fibrous carbon is dispersed.

[0062] The thermoplastic resin used for modification is not particularly limited, but it is preferable to use one or more selected from the group consisting of polyvinyl alcohol, polyacrylic acid, carboxymethyl cellulose, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (P-(VDF-HFP)), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), styrene butadiene rubber (SBR), fluoroolefin copolymer, polyimide, polyamideimide, aramid, phenolic resin, etc., and in particular, thermoplastic resins containing fluorine atoms such as polyvinylidene fluoride (PVDF) and vinylidene fluoride-hexafluoropropylene copolymer (P-(VDF-HFP)) are preferred.

[0063] The melting point of the thermoplastic resin is preferably 50 to 250° C. The lower limit of the melting point of the thermoplastic resin is more preferably 60° C. or higher, more preferably 70° C. or higher, more preferably 80° C. or higher, more preferably 90° C. or higher, and more preferably 100° C. or higher. The upper limit of the melting point of the thermoplastic resin is more preferably 220° C. or lower, more preferably 200° C. or lower, more preferably 180° C. or lower, more preferably 160° C. or lower, and more preferably 150° C. or lower. If the melting point is less than 50°C, the thermoplastic resin particles are likely to aggregate during the process of dispersing them in the electrode sheet, and the heat resistance of the battery is reduced. If the melting point is more than 250°C, there is a risk of deterioration of the active material and solid electrolyte. The glass transition point of the thermoplastic resin is not particularly limited, but is preferably 250° C. or lower. The upper limit of the glass transition point is preferably 200° C. or lower, more preferably 150° C. or lower, more preferably 120° C. or lower, more preferably 100° C. or lower, more preferably 80° C. or lower, more preferably 50° C. or lower, more preferably 40° C. or lower, more preferably 30° C. or lower, more preferably 20° C. or lower, more preferably 10° C. or lower, and more preferably 0° C. or lower.

[0064] The content of fibrous carbon in the electrode sheet of the present invention is 0.1% by mass or more and 10% by mass or less. The lower limit of the content of fibrous carbon is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, even more preferably 1.2% by mass or more, even more preferably 1.5% by mass or more, and particularly preferably 1.8% by mass or more. The upper limit of the content of fibrous carbon is more preferably 6.0% by mass or less, even more preferably 5.0% by mass or less, and particularly preferably 3.0% by mass or less.

[0065] The carbon fiber used in the present invention can be produced, for example, by the method described in WO2009 / 125857. An example is shown below. First, a mesophase pitch composition is prepared in which mesophase pitch is dispersed in a thermoplastic polymer. Next, this mesophase pitch composition is molded in a molten state into a filament or film. Spinning is particularly preferred. By spinning, the mesophase pitch dispersed in the thermoplastic polymer is stretched inside the thermoplastic polymer, and the mesophase pitch composition is converted into fibers to obtain a resin composite fiber. This resin composite fiber has a sea-island structure in which the thermoplastic polymer is the sea component and the mesophase pitch is the island component. The resin composite fiber is then contacted with an oxygen-containing gas to stabilize the mesophase pitch, thereby obtaining a resin composite stabilized fiber. The resin composite stabilized fiber has a sea-island structure with a thermoplastic polymer as a sea component and stabilized mesophase pitch as island components. Next, the thermoplastic polymer, which is the sea component of this resin composite stabilized fiber, is removed and separated to obtain a carbon fiber precursor. Furthermore, this carbon fiber precursor is heated at a high temperature to obtain fibrous carbon (carbon fiber).

[0066] (1-4) Fluorine-based polymers The fluoropolymer used in the electrode sheet of the present invention can be any fluoropolymer having sufficient electrochemical stability. In addition, the fluororesin used in the present invention is preferably one that acts as a binder when forming the electrode sheet and easily forms fibrils by the shear force when forming the sheet. For example, needle-shaped fibers (fibrils) of polytetrafluoroethylene resin can be obtained by applying shear stress to granular polytetrafluoroethylene resin. Conventionally, polytetrafluoroethylene resin has been subjected to shear stress to form needle-shaped fibers, and the needle-shaped fibers are also called fibrillation. When the electrode sheet of the present invention is formed by roll press molding, the shear force can be adjusted by adjusting the press pressure and the speed difference between the rolls. Examples of such fluororesins include polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene, polyvinylidene fluoride, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (P-(VDF-HFP)), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), etc. Two or more of these may be used in combination. Among these, PTFE is particularly preferred because it is easily fibrillated.

[0067] The content of the fluoropolymer in the electrode sheet of the present invention is preferably 0.5 to 25% by mass. The content of the fluoropolymer is preferably 0.8% by mass or more, more preferably 1.0% by mass or more, 1.5% by mass or more, 2.0% by mass or more, and 3.0% by mass or more in this order. The content of the fluoropolymer is preferably 15% by mass or less, more preferably 10% by mass or less, 8% by mass or less, 6% by mass or less, and 5% by mass or less in this order. If it is less than 0.5% by mass, it becomes difficult to maintain the shape of the electrode sheet. If it exceeds 25% by mass, the amount of active material in the electrode becomes small, and the energy density of the obtained battery is likely to decrease.

[0068] The average particle size of the fluoropolymer is preferably 50 to 1000 nm, more preferably 80 to 500 nm, and particularly preferably 100 to 400 nm, and is preferably 0.1 to 10 times, and more preferably 0.5 to 5 times, the average fiber size of the fibrous carbon.

[0069] The fluoropolymer used in the electrode sheet of the present invention is not particularly limited, but it is preferable that at least a part of it is fibrillated in the electrode sheet. The fluoropolymer forms a network structure by its fibril part, and the active material and the conductive assistant are held in the network structure, which contributes to sheet formation and allows the formation of an electrode sheet with high tensile breaking strength. In one embodiment of the present invention, it is presumed that at least a part of the fibrous carbon contacts the fibrils, is incorporated into the network structure, or is entangled with the fibrils, and forms a conductive path in the thickness direction of the electrode sheet. Therefore, it is considered that the fibrous carbon exhibits not only high tensile breaking strength but also excellent electrical conductivity in the thickness direction.

[0070] (1-5) Carbon-based conductive additives other than fibrous carbon The electrode sheet of the present invention may contain a carbon-based conductive assistant in addition to the above-mentioned fibrous carbon. Examples of carbon-based conductive assistants other than fibrous carbon include carbon black, acetylene black, scaly carbon, graphene, graphite, and carbon nanotubes (CNTs). These carbon-based conductive assistants may be used alone or in combination of two or more.

[0071] The shape of these carbon-based conductive assistants is not particularly limited, but spherical particles such as carbon black and acetylene black are preferred. The average particle size (primary particle size) of the carbon-based conductive assistant is preferably 10 to 200 nm, more preferably 20 to 100 nm. The aspect ratio of these carbon-based conductive assistants is 10 or less, preferably 1 to 5, more preferably 1 to 3. The content of the carbon-based conductive assistant other than fibrous carbon in the electrode sheet of the present invention is preferably 0.1 to 4 mass % relative to the electrode sheet, more preferably 0.5 to 3 mass %, and even more preferably 1 to 2 mass %.

[0072] When the conductive assistant contains the above-mentioned fibrous carbon and a carbon-based conductive assistant other than the fibrous carbon, from the viewpoint of achieving both electronic conductivity and ionic conductivity, it is preferable that the mass ratio of the fibrous carbon in the conductive assistant is 20 mass% or more and 99 mass% or less, and the mass ratio of the carbon-based conductive assistant other than the fibrous carbon is 1 mass% or more and 80 mass% or less. It is more preferable that the mass ratio of the fibrous carbon is 40 mass% or more and 99 mass% or less, and the mass ratio of the carbon-based conductive assistant other than the fibrous carbon is 1 mass% or more and 60 mass% or less. The mass ratio of the fibrous carbon is preferably 50 mass% or more, more preferably 60 mass% or more, more preferably 70 mass% or more, more preferably 80 mass% or more, and particularly preferably 85 mass% or more. The mass ratio of the carbon-based conductive assistant other than the fibrous carbon is preferably 50 mass% or less, more preferably 40 mass% or less, more preferably 30 mass% or less, more preferably 20 mass% or less, and particularly preferably 15 mass% or less. A small amount of the carbon-based conductive assistant other than the fibrous carbon is considered to act as a cushion to buffer the volume change of the active material due to repeated charge and discharge cycles.

[0073] (1-6) Other When the electrode sheet of the present invention is used in an all-solid-state lithium ion secondary battery, it may contain a solid electrolyte. The solid electrolyte may be selected from conventionally known materials. For example, sulfide-based solid electrolytes, oxide-based solid electrolytes, hydride-based solid electrolytes, and polymer electrolytes can be mentioned. In the present invention, it is preferable to use a sulfide-based solid electrolyte because it has high lithium ion conductivity.

[0074] A specific example of the sulfide-based solid electrolyte is a sulfide-based solid electrolyte (Li-AS) consisting of Li, A, and S. In the sulfide-based solid electrolyte Li-AS, A is at least one selected from the group consisting of P, Ge, B, Si, Sb, and I. A specific example of such a sulfide-based solid electrolyte Li-AS is Li7P3S 11, 70Li2S-30P2S5, LiGe 0.25 P 0.75 S4, 75Li2S-25P2S5, 80Li2S-20P2S5, Li 10 GeP2S 12 , Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 , Li2S-SiS2, Li6PS5Cl, etc., and Li7P3S in particular is preferred due to its high ionic conductivity. 11 is preferred.

[0075] Specific examples of hydride-based solid electrolytes include complex hydrides of lithium borohydride, such as LiBH4-LiI complex hydrides, LiBH4-LiNH2 complex hydrides, LiBH4-P2S5, and LiBH4-P2I4.

[0076] The solid electrolytes may be used alone or in combination of two or more kinds, if necessary.

[0077] (2) Manufacturing method of electrode sheet The electrode sheet of the present invention can be manufactured, for example, by mixing the above-mentioned active material, carbon-based conductive assistant, and fluoropolymer in a powder state to prepare a powder mixture, and then pressure-molding the powder mixture into a film using a rolling device having a first roll and a second roll. The fluoropolymer is used in a fibrillated state, which makes it easier to maintain the sheet shape and forms a self-supporting, i.e., self-supporting, film. The fluoropolymer may be fibrillated in advance, may be fibrillated when the powder mixture is mixed, or may be fibrillated when pressure-molded into a film. From the viewpoint that the strength of the electrode sheet is increased by the intertwining of fibril parts generated from the particles of the fluoropolymer, it is preferable to fibrillate the powder mixture when mixing it, or to fibrillate the powder mixture when pressure-molded into a film. In addition, a volatile solvent such as alcohol may be added when mixing the powder.

[0078] Examples of methods for fibrillating a fluoropolymer include applying shear to the fluoropolymer particles during powder mixing, and applying shear to the fluoropolymer particles by creating a speed difference between the first roll and the second roll during pressure molding.

[0079] The fiber diameter of the fibril portion generated from the fluoropolymer particles is preferably 200 nm or less, more preferably 100 nm or less, even more preferably 80 nm or less, and particularly preferably 60 nm or less. It is also preferably 1 / 2 or less, more preferably 1 / 3 or less, of the particle diameter of the fluoropolymer. Furthermore, it is preferably 1 / 2 or less, more preferably 1 / 3 or less, of the fiber diameter of the fibrous carbon blended together.

[0080] The fiber length of the fibril portion generated from the fluoropolymer particles is preferably 1 μm or more, more preferably 2 μm or more, and further preferably 1 / 10 or more, more preferably 1 / 3 or more of the average fiber length of the fibrous carbon blended therewith.

[0081] The electrode sheet for lithium ion secondary batteries of the present invention does not have a slurry application step in its manufacturing process, so the fibrous carbon used as a conductive additive is less likely to be oriented in one direction, and it is expected that the sheet will have excellent conductivity in the film thickness direction and be less likely to have anisotropy in mechanical strength. Furthermore, since no binder dissolved in a solvent is used, the active material and the conductive additive are easily in direct contact with each other. In addition, since the active material and the conductive additive are supported by the fluoropolymer fibers that function as a binder, high ionic and electronic conductivity can be maintained even if the volume of the active material changes due to charging and discharging. Therefore, it is expected that a lithium-ion secondary battery with reduced battery electrode resistance and excellent cycle characteristics can be provided. EXAMPLES

[0082] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Various measurements and analyses in the examples were carried out according to the following methods.

[0083] (Confirmation of the shape of fibrous carbon) The fiber length of the fibrous carbon was measured by dispersing the fibrous carbon (sample) in 1-methyl-2-pyrrolidone and dispersing the dilute dispersion with an image analysis particle size distribution analyzer (Model IF-200nano, manufactured by Jusco International Co., Ltd.). The average fiber length of the fibrous carbon is the average value based on the number of pieces. The fiber diameter of the fibrous carbon was observed and photographed using a scanning electron microscope (S-2400 manufactured by Hitachi, Ltd.), 300 points were randomly selected from the obtained electron microscope photographs to measure the fiber diameter, and the average value of all the measurement results (n=300) was taken as the average fiber diameter. In addition, the average aspect ratio was calculated from the average fiber length and the average fiber diameter.

[0084] (X-ray diffraction measurement of carbon fiber) X-ray diffraction measurements were performed using Rigaku RINT-2100 in accordance with JIS R7651, and the lattice spacing (d002) and crystallite size (Lc002) were measured.

[0085] (Method for measuring powder volume resistivity) The powder volume resistivity was measured using a four-probe electrode unit under a load of 0.02 to 2.50 kN using a powder resistivity system (MCP-PD51) manufactured by Mitsubishi Chemical Analytech Co., Ltd. The volume resistivity was measured at a packing density of 0.8 g / cm3 from the relationship diagram of the volume resistivity with respect to the change in packing density. 3 The volume resistivity value at this time was taken as the powder volume resistivity of the sample.

[0086] (Measurement of particle size of fluoropolymer) The particle size of the fluoropolymer was measured by observing and photographing it using a scanning electron microscope (S-2400 manufactured by Hitachi, Ltd.). 300 points were randomly selected from the obtained electron microscope photographs to measure the particle size, and the average value of all the measurement results (n=300) was taken as the average particle size.

[0087] (Electrode sheet tensile strength, film thickness) The electrode sheet was cut into a width of 1 cm, and the tensile breaking strength was measured using a digital force gauge (FGP-10, manufactured by SHIMPO).

[0088] (Electrical Conductivity) The electrode resistance in the film thickness direction of the fabricated electrode was measured using a potentiostat / galvanostat (HA-151B manufactured by Hokuto Denko Corporation), and the electrical conductivity calculated from the resistance value is shown in Table 1.

[0089] (Mesophase pitch manufacturing method) The coal tar pitch with a softening point of 80°C from which the quinoline insoluble matter had been removed was hydrogenated in the presence of a Ni-Mo catalyst at a pressure of 13 MPa and a temperature of 340°C to obtain a hydrogenated coal tar pitch. This hydrogenated coal tar pitch was heat-treated at 480°C under normal pressure, and then the pressure was reduced to remove the low boiling point components to obtain a mesophase pitch. This mesophase pitch was filtered using a filter at a temperature of 340°C to remove foreign matter in the pitch, and a refined mesophase pitch was obtained.

[0090] (Manufacturing method of fibrous carbon (CNF)) A mesophase pitch composition was prepared by melt-kneading 60 parts by mass of linear low-density polyethylene (EXCEED (registered trademark) 1018HA, manufactured by ExxonMobil, MFR = 1 g / 10 min) as a thermoplastic resin and 40 parts by mass of mesophase pitch (mesophase ratio 90.9%, softening point 303.5°C) obtained by the above-mentioned mesophase pitch manufacturing method in a co-rotating twin-screw extruder (Toshiba Machine Co., Ltd.'s "TEM-26SS", barrel temperature 300°C, under nitrogen gas flow). Next, this mesophase pitch composition was melt spun at a spinneret temperature of 360° C. to form long fibers having a fiber diameter of 90 μm. The mesophase pitch-containing fiber bundle obtained by the above operation was held in air at 215°C for 3 hours to stabilize the mesophase pitch, and a stabilized mesophase pitch-containing fiber bundle was obtained. The stabilized mesophase pitch-containing fiber bundle was subjected to nitrogen replacement in a vacuum gas replacement furnace, then reduced in pressure to 1 kPa, and held at 500°C for 1 hour under the reduced pressure to remove the thermoplastic resin, thereby obtaining a stabilized fiber. The stabilized fiber was then carbonized by holding at 1000° C. for 30 minutes in a nitrogen atmosphere, and further graphitized by heating to 1500° C. in an argon atmosphere and holding for 30 minutes. The graphitized carbon fiber aggregate was then pulverized to obtain a powdered carbon fiber aggregate. The carbon fibers had a linear structure with no branches.

[0091] The obtained carbon fiber had no branching confirmed by SEM photographs (branching degree was 0.00). The crystallite plane spacing d002 was 0.3441 nm, the crystallite size Lc002 was 5.4 nm, the average fiber diameter was 270 nm, the average fiber length was 15 μm, the average aspect ratio was 56, and the average fiber length was 0.8 g / cm. 3 The powder volume resistivity is 0.0277 Ω cm and the specific surface area is 10 m 2 / g. The metal content was less than 20 ppm.

[0092] (Surface modification of fibrous carbon (i)) 1 part by mass of P-(VDF-HFP) (Kynar 2500-20 manufactured by Arkema) was dissolved in acetone, and 3 parts by mass of fibrous carbon was dispersed therein to prepare a dispersion liquid. The dispersion liquid was spray-dried using a spray dryer (SB39 manufactured by PRIS), and the surface of the fibrous carbon was modified with P-(VDF-HFP) (hereinafter, abbreviated as resin-bonded fiber (i)).

[0093] (Surface modification of fibrous carbon (ii)) The surface of the fibrous carbon was modified with VDF-HFP copolymer in the same manner as in surface modification of the fibrous carbon (i), except that the amount of fibrous carbon to be dispersed was 9 parts by mass (hereinafter referred to as resin-bonded fiber (ii)).

[0094] Example 1 90 parts by mass of LiFePO4 as an active material, 5 parts by mass of polytetrafluoroethylene (PTFE) with an average particle diameter of 200 nm as fluorine-based polymer particles, and 5 parts by mass of the fibrous carbon produced above as a carbon-based conductive assistant were mixed, and further sheared using a mortar. This mixture was repeatedly pressed using a roll press to form it into a sheet. The film thickness of the obtained electrode sheet was 188 μm, and the tensile breaking strength was 0.32 N / mm 2 The electrical conductivity of this electrode sheet in the thickness direction was 2.7 × 10 -3 The surface area of ​​the electrode sheet was 1.2 S / cm, and the porosity was 39 volume%. At least a portion of the PTFE was fibrillated, with a fiber diameter of approximately 50 nm. Figure 1 shows an SEM photograph of the surface of this electrode sheet, and Figure 2 shows an SEM photograph of the cross section of the electrode sheet. These SEM photographs confirm the presence of fibrillated PTFE in addition to fibrous carbon.

[0095] Example 2 An electrode sheet was obtained in the same manner as in Example 1, except that 87 parts by mass of LiFePO4 was used as the active material, 10 parts by mass of polytetrafluoroethylene (PTFE) having an average particle size of 200 nm was used as the fluorine-based polymer particles, and 3 parts by mass of the fibrous carbon produced above was used as the carbon-based conductive assistant. Various physical properties are shown in Table 1. An SEM photograph of the surface of this electrode sheet is shown in FIG. 3, and an SEM photograph of the cross section of the electrode sheet is shown in FIG. 4. These SEM photographs show that there is more fibrillated PTFE than in Example 1, and it can also be confirmed that the fibrillated PTFE supports the active material particles and the fibrous carbon, and that the fibrillated PTFE and the fibrous carbon are entangled.

[0096] Comparative Example 1 The fibrous carbon was acetylene black (hereinafter sometimes abbreviated as "AB"; "Denka Black" (registered trademark), manufactured by Denka Co., Ltd., 75% pressed product, average particle size: 0.036 μm, specific surface area: 65 m 2 An electrode sheet was obtained in the same manner as in Example 1, except that the amount of PTFE was changed to 0.05 wt. / g. Various physical properties are shown in Table 1. An SEM photograph of the surface of this electrode sheet is shown in FIG. 5, and an SEM photograph of the cross section of the electrode sheet is shown in FIG. 6. These SEM photographs confirm that the fibrillated PTFE supports the particulate matter.

[0097] Comparative Example 2 A slurry was prepared by mixing 90 parts by mass of LiFePO4 as an active material, 5 parts by mass of polytetrafluoroethylene (PTFE) having an average particle diameter of 200 nm as fluorine-based polymer particles, 5 parts by mass of the fibrous carbon produced above as a carbon-based conductive assistant, and 230 parts by mass of water as a solvent. An electrode sheet was prepared by applying this slurry onto a current collector and drying it. An SEM photograph of the surface of this electrode sheet is shown in FIG. 7. According to this SEM photograph, no fibrous material other than the fibrous carbon could be observed. In other words, it can be confirmed that no fibrillated PTFE is present. The obtained electrode sheet could not maintain its sheet shape, and various physical properties could not be measured.

[0098] Example 3 Except for changing the film thickness to 404 μm, an electrode sheet was obtained in the same manner as in Example 1. Various physical properties are shown in Table 1. Even when the film thickness was increased, the electrical conductivity did not decrease.

[0099] Example 4 An electrode sheet was obtained in the same manner as in Example 1, except that the carbon-based conductive assistant was 4 parts by mass of the fibrous carbon produced above and 1 part by mass of AB. Various physical properties are shown in Table 1. By using another carbon-based conductive assistant in combination, the electrical conductivity was further improved.

[0100] Example 5 An electrode sheet was obtained in the same manner as in Example 1, except that 92 parts by mass of LiFePO4 was used as the active material and 3 parts by mass of the fibrous carbon produced above was used as the carbon-based conductive assistant. Various physical properties are shown in Table 1.

[0101] Example 6 An electrode sheet was obtained in the same manner as in Example 1, except that 93 parts by mass of LiFePO4 was used as the active material and 2 parts by mass of the fibrous carbon produced above was used as the carbon-based conductive assistant. Various physical properties are shown in Table 1.

[0102] Example 7 An electrode sheet was obtained in the same manner as in Example 1, except that the resin-bonded fiber (i) produced by the surface modification of the fibrous carbon (i) was used as the carbon-based conductive assistant. Various physical properties are shown in Table 1. The breaking strength was high because the resin-bonded fiber (i) was used.

[0103] Example 8 An electrode sheet was obtained in the same manner as in Example 1, except that the resin-bonded fiber (ii) produced by the surface modification of the fibrous carbon (ii) was used as the carbon-based conductive assistant. Various physical properties are shown in Table 1. The breaking strength was high because the resin-bonded fiber (ii) was used.

[0104] [Table 1]

Claims

1. An electrode sheet for a lithium ion secondary battery, comprising at least an active material for a lithium ion battery, fibrous carbon, and a fluorine-based polymer, The fluoropolymer is partially or entirely fibrillated, The electrode sheet for lithium ion secondary batteries has a thickness of 50 to 2000 (μm) and a tensile breaking strength of 0.20 (N / mm 2 ) and The average fiber diameter of the fibrous carbon is 100 to 900 (nm), The electrode sheet for lithium ion secondary batteries, wherein the content of the fibrous carbon in the electrode sheet for lithium ion secondary batteries is 0.1 to 10 (mass %).

2. An electrode sheet for a lithium ion secondary battery, comprising at least an active material for a lithium ion battery, fibrous carbon, and a fluorine-based polymer, The lithium ion secondary battery electrode sheet has a thickness of 50 to 2000 (μm) and a tensile breaking strength of 0.20 (N / mm 2 ) or more; The average fiber diameter of the fibrous carbon is 100 to 900 (nm), the content of the fibrous carbon in the lithium ion secondary battery electrode sheet is 0.1 to 10 (mass%), The tensile breaking strength (N / mm 2 The product of the thickness (mm) and the thickness (mm) is 0.04 (N / mm) or more.

3. The electrode sheet for a lithium ion secondary battery according to claim 1 or 2, further comprising a carbon-based conductive assistant other than the fibrous carbon.

4. The electrode sheet for lithium ion secondary batteries according to claim 1 or 2, wherein the average fiber length of the fibrous carbon is 10 to 50 (μm).

5. The packing density of the fibrous carbon is 0.8 (g / cm 3 ) powder volume resistivity was 4.00×10 -2 3. The electrode sheet for lithium ion secondary batteries according to claim 1 or 2, wherein the electrical conductivity is 0.1 (Ω·cm) or less.

6. 3. The electrode sheet for a lithium ion secondary battery according to claim 1, wherein the fluorine-based polymer is polytetrafluoroethylene.

7. The electrode sheet for lithium ion secondary batteries according to claim 1 or 2, wherein the porosity of the electrode sheet for lithium ion secondary batteries is 5 to 60 (volume%).

8. The electrical conductivity in the thickness direction of the electrode sheet for lithium ion secondary batteries is 8.0×10 -4 The electrode sheet for lithium ion secondary batteries according to claim 1 or 2, wherein the electrical conductivity is 100% or more.

Citation Information

Patent Citations

  • Cathode for lithium-containing batteries and method for producing the same without solvents

    JP2015508220A

  • Pitch-based extra fine carbon fiber, electrode mixture layer for nonaqueous electrolyte secondary battery, electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    JP2017066546A

  • Fibrous carbon-containing electrode mixture layer for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery electrode including the same, and nonaqueous electrolyte secondary battery

    JP2018049837A

  • Electrode for energy storage device and method for manufacturing dry electrode film for energy storage device

    JP2019512872A

  • Dry film manufacturing method, rolling device, dry film, and substrate coated with dry film

    JP2020522090A